AUGMENTED REALITY DANCE LEARNING MEDIA: LABAN NOTATION MOVEMENT LITERACY FOR JUNIOR HIGH SCHOOL STUDENTS: AUGMENTED REALITY DANCE LEARNING MEDIA: LABAN NOTATION MOVEMENT LITERACY FOR JUNIOR HIGH SCHOOL STUDENTS - Fatmasari, Siti; Triana, Dinny Devi; Jeon, Jeong OK (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study aims to introduce dance learning media using Augmented Reality with Movement Literacymaterial based on Laban Notation symbols for junior high school students. The background of thestudy is based on the low interest of students in learning dance and difficulties in understanding theelements of space, time, and energy due to the limitations of conventional media that are not inaccordance with the characteristics of the digital generation. The method used is research anddevelopment (R&D) with initial stages including needs analysis, product design, productdevelopment, implementation through limited trials, and product evaluation. The product developedis an Augmented Reality (AR) application that presents movement literacy based on Laban Notationin an interactive 3D form, so that students can learn movement visually, kinesthetically, andreflectively. Initial results based on needs analysis and the designed product show that theapplication is considered interesting, easy to use, and helps understand basic dance movements, andis in accordance with the characteristics of students in the digital era. Teachers gave positiveresponses to the potential of this media as a supporter of deep learning that is conscious, meaningful,and enjoyable. Thus, it is hoped that the AR-Motion Literacy application can be an innovativealternative in dance learning, especi